2022
DOI: 10.1111/1751-2980.13139
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic, clinicopathological, and growth characteristics of minute gastric cancer

Abstract: Objective To clarify the endoscopic, clinicopathological, and growth characteristics of minute gastric cancer (MGC) and to improve its detection rate. Methods Patients with early gastric cancer who underwent endoscopic submucosal dissection from July 2012 to September 2021 were retrospectively reviewed. MGC was defined as gastric cancer of 5 mm or less in size. Preoperative and postoperative endoscopic and pathological data were collected and analyzed. Follow‐up information was collected until 9 April 2022. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…We noticed that the median largest tumour size of 4 cm in metachronous gastric cancer was too large considering the median diagnosis interval of 3 years between primary gastric lymphoma and metachronous gastric cancer. A study of minute gastric cancer also showed that the mean growth rate was 0.0071 mm/day, and it took an average of 3.42 years to grow to 5 mm, with 95% of cases being well-differentiated tubular adenocarcinoma [ 34 ]. One possible reason for the larger tumour size of the metachronous gastric cancers in our study is that some gastric cancers may have been present before or at the time of diagnosis of primary gastric lymphoma but were missed.…”
Section: Discussionmentioning
confidence: 99%
“…We noticed that the median largest tumour size of 4 cm in metachronous gastric cancer was too large considering the median diagnosis interval of 3 years between primary gastric lymphoma and metachronous gastric cancer. A study of minute gastric cancer also showed that the mean growth rate was 0.0071 mm/day, and it took an average of 3.42 years to grow to 5 mm, with 95% of cases being well-differentiated tubular adenocarcinoma [ 34 ]. One possible reason for the larger tumour size of the metachronous gastric cancers in our study is that some gastric cancers may have been present before or at the time of diagnosis of primary gastric lymphoma but were missed.…”
Section: Discussionmentioning
confidence: 99%